BATOMBE: WARISAN BUDAYA BANGSA DARI NAGARI ABAI PROVINSI SUMATERA BARAT - Eva Krisna (Balai Bahasa Provinsi Riau, 2016)
“Batombe” is an oral tradition of the Nagari Abai society at Sangir BatanghariSubdistrict, South Solok District, West Sumatra Province. Batombe is exchanging rhymes (berbalas pantun) which is performed as an entertainment on the wedding party (baralek). Batombe is identical with Great House (Rumah Gadang) Nagari Abai which is a unique house because it is a long traditional custom house that has many rooms. It reaches 21 rooms. The rhymes in batombe tends to deliver a feeling of lilting so the singers often drift into the atmosphere of the show. Therefore, as part of community life, batombe often cause a negative effects for the singers soul. This paper describes various things, such as: who batombe singer is; the time to perform this activity; the relationship between batombe and Great House (Rumah Gadang) at Nagari Abai; and the negative effects caused by batombe for the singers. This paper based on the fact that in oral tradition there is a close relationship between text and the speakers and text with context (place, time and atmosphere), a multidisciplinary approach is used in this paper, such as historical, sociological, anthropological, and psychological approach. The method used is descriptiveanalysis method.